2003
DOI: 10.1007/s00264-003-0468-3
|View full text |Cite
|
Sign up to set email alerts
|

Late-term reconstruction of lateral ankle ligaments using a split peroneus brevis tendon graft (Colville's technique) in patients with chronic lateral instability of the ankle

Abstract: We reviewed 14 patients with chronic lateral instability of the ankle treated by Colville's technique between 1996 and 2001. The mean patient age was 25 (20-35) years and all were men. The mean period between injury and surgery was 25 (18-32) months, and the mean follow-up was 20 (14-32) months. Twelve of the results were excellent and two were good according to the criteria of Chrisman and Snook. All patients returned to normal daily activity levels at an average of 6 months following surgery. Résumé

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…Results are dependent on various factors, for example, the position of the patient's foot, the force applied to the foot and its ability to withstand the force, etc. In fact, we lack the criteria to distinguish tears of one ligament from those of a combination of ligaments [4,5,14,19,22,24,25]. In Table 1 Mean values of clinical Good score prior to and one year after surgery with standard deviations; patients sorted according to age detecting an injury of the ATFL and/or CFL it is also important to document their exact extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are dependent on various factors, for example, the position of the patient's foot, the force applied to the foot and its ability to withstand the force, etc. In fact, we lack the criteria to distinguish tears of one ligament from those of a combination of ligaments [4,5,14,19,22,24,25]. In Table 1 Mean values of clinical Good score prior to and one year after surgery with standard deviations; patients sorted according to age detecting an injury of the ATFL and/or CFL it is also important to document their exact extent.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main views with respect to treatment. The first group favours primary surgical repair [3,12,13,15,17,23,25], whilst the second prefers conservative treatment [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with recurrent injuries and repetitive sprains. 5,6 Ankle injuries can affect medial and lateral ligaments, but lateral ligament injuries are more common: 85% of ankle injuries involve the lateral ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…9,13 Common complications of surgery include numbness, hyperesthesia, crepitus, pain, and instability. 5,9,13 A Cochrane review of 20 randomized controlled trials involving 2262 patients found insufficient evidence to determine the relative effectiveness of surgery versus conservative therapy for lateral ankle injuries. 16 We found no evidence regarding the relative effectiveness of surgery versus conservative therapy for peroneal injuries.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation